Athletic protocol in non-cystic fibrosis-related bronchiectasis: rationale and design of the pilot ATHOS study - Bertuccio, Francesco; Tafa, Mitela; Carabetta, Denise; Gemelli, Tiziano; D’Antona, Giuseppe; Crisafulli, Oscar; Conio, Valentina; Grosso, Amelia; De Silvestri, Annalisa; Corsico, Angelo G.; Stella, Giulia M. (Frontiers in Medicine, 2025)
Bronchiectasis is a chronic and heterogeneous respiratory condition, which is characterized by irreversible abnormal dilatation of the bronchial tree, chronic cough, copious sputum production, and increased risk of acute exacerbations that contribute to the development of chronic respiratory failure, poor exercise tolerance and, consequently, poor quality of life (QoL). A large amount of published data explore regarding the diagnostic approach, the clinical management, and the development of novel therapeutic strategies. Moreover, it is well-known that the exercise-training rehabilitation can be helpful in reducing disease deterioration and relieve symptoms. However, the effect of exercise in patients with non-cystic fibrosis-related bronchiectasis (NCFB) is scarce, and no athletic programs have been fully developed. Thus, the aim of the present study is to investigate the results obtained by administering a specific athletic/physical protocol to these patients. Among all patients affected by NCFB and followed in our Institution, those with the highest scores of performance status will be addressed to the Interdipartimental Centre in Motor and Sport Activities, Sport Medicine Centre, University of Pavia for a work protocol based on mesocycles of 3 times/week for 6 months. A patient-tailored active training regimen will be set up considering major complaints—endurance training for patients with dyspnea, strength training for patients with cough and difficult sputum expectoration, and a balanced aerobic and anaerobic training for patients with asthenia. To the best of our knowledge, the ATHOS study is the first perspective clinical trial, encompassing athletic programs for non-CF bronchiectasis patients, and rationale and in itinere, partial results will be presented, analyzed, and discussed in comparison to standard disease management.